Genome-wide chromatin interaction profiling reveals a vital role of super-enhancers and rearrangements in host enhancer contacts during BmNPV infection - Zhao, Shudi; Li, Yuedong; Chen, Guanping; Wang, Xingyang; Chen, Nan; Wu, Xiaofeng

(untitled) (Genome Research, 2023)
As influential regulatory elements in the genome, enhancers control gene expression under specific cellular conditions, and such connections are dynamic under different conditions. However, because of the lack of a genome-wide enhancer–gene connection map, the roles and regulatory pattern of enhancers were poorly investigated in insects, and the dynamic changes of enhancer contacts and functions under different conditions remain elusive. Here, combining Hi-C, ATAC-seq, and H3K27ac ChIP-seq data, we generate the genome-wide enhancer–gene map of silkworm and identify super-enhancers with a role in regulating the expression of vital genes related to cell state maintenance through a sophisticated interaction network. Additionally, a radical attenuation of chromatin interactions is found after infection of Bombyx mori nucleopolyhedrovirus (BmNPV), the main pathogen of silkworm, which directly rearranges the enhancer contacts. Such a rearrangement disturbs the intrinsic enhancer–gene connections in several antiviral genes, resulting in reduced expression of these genes, which accelerates viral infection. Overall, our results reveal the regulatory role of super-enhancers and shed new light on the mechanisms and dynamic changes of the genome-wide enhancer regulatory network.